Developing capacity-building activities for mental health system strengthening in low- and middle-income countries for service users and caregivers, service planners, and researchers. (2nd October 2017) - Semrau, M.; Alem, A.; Abdulmalik, J.; Docrat, S.; Evans-Lacko, S.; Gureje, O.; Kigozi, F.; Lempp, H.; Lund, C.; Petersen, I.; Shidhaye, R.; Thornicroft, G.; et al.
Abstract : There is increasing international recognition of the need to build capacity to strengthen mental health systems. This is a fundamental goal of the 'Emerging mental health systems in low- and middle-income countries' (Emerald) programme, which is being implemented in six low- and middle-income countries (LMICs) (Ethiopia, India, Nepal, Nigeria, South Africa, Uganda). This paper discusses Emerald's capacity-building approaches and outputs for three target groups in mental health system strengthening: (1) mental health service users and caregivers, (2) service planners and policy-makers, and (3) mental health researchers. When planning the capacity-building activities, the approach taken included a capabilities/skills matrix, needs assessments, a situational analysis, systematic reviews, qualitative interviews and stakeholder meetings, as well as the application of previous theory, evidence and experience. Each of the Emerald LMIC partners was found to have strengths in aspects of mental health system strengthening, which were complementary across the consortium. Furthermore, despite similarities across the countries, capacity-building interventions needed to be tailored to suit the specific needs of individual countries. The capacity-building outputs include three publicly and freely available short courses/workshops in mental health system strengthening for each of the target groups, 27 Masters-level modules (also open access), nine Emerald-linked PhD students, two MSc studentships, mentoring of post-doctoral/mid-level researchers, and ongoing collaboration and dialogue with the three groups. The approach taken by Emerald can provide a potential model for the development of capacity-building activities across the three target groups in LMICs.